UPAYA MENGATASI KESULITAN PADA PASSING BAWAH MELALUI VARIASI LATIHAN DI KELAS V SDN BETET 3 KOTA KEDIRI - Novian Rizki Galang Pamungkas; M. Akbar Husein Allsabah; Moh. Aan Zainul Arifin (JOURNAL SAINS STUDENT RESEARCH, 2025)
As a student of volleyball, you should make it a priority to learn the underhand pass and other fundamental passing methods. On the other hand, many fifth graders at SDN Betet 3 in Kediri City struggle to use this strategy in real life. Through regular training changes, this research seeks to address these problems. Two cycles of Classroom Action Research (CAR) were used as the research approach. Students' underhand passing abilities improved significantly after receiving several training modifications, according to the findings. The number of students who successfully executed underhand passes increased from the first to the second cycle, indicating that the research was successful. Therefore, it is reasonable to assume that pupils' underhand passing abilities may be enhanced via the use of training variants.